2010
DOI: 10.1007/s13353-010-0022-0
|View full text |Cite
|
Sign up to set email alerts
|

The −112G > A polymorphism of the secretoglobin 3A2 (SCGB3A2) gene encoding uteroglobin-related protein 1 (UGRP1) increases risk for the development of Graves’ disease in subsets of patients with elevated levels of immunoglobulin E

Abstract: The human secretoglobin 3A2 (SCGB3A2) gene encoding secretory uteroglobin-related protein 1 (UGRP1) resides on the chromosome region 5q31-33 that harbors a susceptibility locus to several autoimmune and inflammatory diseases, including asthma and Graves' disease (GD). Recently, association between the marker rs1368408 (-112G >A), located in the promoter region of the SCGB3A2 gene, and susceptibility to GD was found in Chinese and UK Caucasians. The study aim was to evaluate whether this polymorphism confers GD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
12
1
Order By: Relevance
“…This was confirmed and extended by Song et al who showed that lower expression from haplotypes encoding rs1368408 A was associated with lower concentration of SCGB3A2 mRNA also in thyroid tissue [158]. Further support for functional significance of the rs1368408 A variant comes from its association with reduced concentration of UGRP1 in serum of healthy subjects as well as of patients with GD or asthma [161,164]. The functional effect of the A allele of rs1368408 may occur through disruption of the binding site for CCAAT/enhancer-binding protein α (C/EBPα) which positively regulates transcription of SCGB3A2 [158,165].…”
Section: Genes Predisposing To Gdmentioning
confidence: 55%
See 2 more Smart Citations
“…This was confirmed and extended by Song et al who showed that lower expression from haplotypes encoding rs1368408 A was associated with lower concentration of SCGB3A2 mRNA also in thyroid tissue [158]. Further support for functional significance of the rs1368408 A variant comes from its association with reduced concentration of UGRP1 in serum of healthy subjects as well as of patients with GD or asthma [161,164]. The functional effect of the A allele of rs1368408 may occur through disruption of the binding site for CCAAT/enhancer-binding protein α (C/EBPα) which positively regulates transcription of SCGB3A2 [158,165].…”
Section: Genes Predisposing To Gdmentioning
confidence: 55%
“…Association between GD and the A allele of rs1368408 (OR=1.18, P=0.007) was independently confirmed in a similarly sized UK cohort (SNP75 was found to have low polymorphism and was not analyzed) [160]. Recently, further evidence for association between rs1368408 and GD was provided by a study in a Russian cohort (~1500 cases and controls, OR=1.33, P=2.9×10 -5 ) [161]. It should be noted that a relatively early study in a Chinese population did not observe the effect of rs1368408 although this might have been caused by low power due to limited numbers of subjects (~200 cases and controls) [162].…”
Section: Genes Predisposing To Gdmentioning
confidence: 97%
See 1 more Smart Citation
“…Further developments in genotyping technology, moving from PCR-RFLP based methods to faster and more cost effective fluorescent probes has enabled larger numbers of SNPs to be interrogated in a single study. In addition, collection of larger AITD cohorts by several investigators provided greater power to detect regions of association, which was important, considering the modest magnitudes of effect anticipated (OR=1.2-1.5) [50-52]. These advances have facilitated comprehensive SNP screening and enabled both novel disease gene identification and refining of association signals by interrogating a dense set of common SNPs to narrow down the location of the aetiological variant.…”
Section: Later Days Of Aitd Gene Discovery and Refining Association Smentioning
confidence: 99%
“…Similarly, UGRP1 has been suggested to exhibit anti-inflammatory functions. It has been shown that UGRP1 is associated with an increased risk for Graves’ disease (17,18). However, there have been confounding results with regard to the correlation between UGRP1 gene polymorphisms and asthma risk (5,7,9,19).…”
Section: Discussionmentioning
confidence: 99%